Quality and integrity of the data used for the measurement of scientific output. Study Case: CvLAC Platform (Colombia) (LACCEI, 2024)
Each country uses different technological mechanisms for the evaluation of its technological capabilities, however, in the great majority of Latin America, platforms are used that are not very interoperable and that require the input of information by the researchers, who are already bad practices or involuntary errors comment on continuous failures that affect the measurements of countries. For the study case, an information extraction mechanism was developed for the CvLAC platform of the Ministry of Science of Colombia, to obtain data reported by some profiles of researchers. Subsequent to the analysis, a significant failure in the process is evidenced, obtaining that 65.3% of the studied records present errors in the reported data. For the above it was concluded that an interoperable platform is required with systems such as ORCID or CrossRef to automatically select or associate the production of researchers directly from the editorials.